Development of a novel wireless telemetric brain stimulator for behavioral studies in rodents - V. Milner Paul; Jijo Francis; Smriti Menon; Loitongbam Surajkumar Singh; Adarsh V. Parekkattil; Shuma Adhikari (Ain Shams Engineering Journal)
Brain simulators are moving the field of neuroscience at a rapid pace due to their wide applicability in treating neurodegenerative disorders. Although continuing advances in the field have made significant breakthroughs, most brain simulators remain too expensive for general clinical applications We developed a user friendly, cost effective, multi-channel wireless brain stimulator that delivers output with high precision. The multichannel output of this device makes it amenable to conducting behavioral studies on different regions of the brain in rodents. The efficacy of our head-mountable device is substantiated by conducting intracranial and intracortical experiments in rats. We tested the output of the device by changing the ifrequency (100 Hz–400 Hz), amplitude, pulse width and current (10 µA – 1 mA) of the stimulator by altering the ON time period of the pulses and resistor values. We have defined optimum frequency (140 Hz) for the intracranial experiment and lower and upper threshold currents for the intracortical experiment. The successful feasibility of this device has been demonstrated invivo in rats and invitro in saline solution. Real-time experiments like Intracranial Self Stimulation (ICSS) and Intracortical Microstimulation (ICMS) tests were successful during the animal experiment to evaluate this brain stimulator. Our device has widespread applicability in conducting behavior-based studies and deriving insights into various mechanistic pathways in rodent brain.